1997
DOI: 10.1210/endo.138.10.5451
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Stimulates Both Leptin Secretion and Production by Rat White Adipose Tissue

Abstract: Leptin, the peptide encoded by the obese gene, is secreted by adipose cells and plays a role in regulating food intake, energy expenditure, and adiposity. Because earlier studies suggested that insulin increases the expression of leptin, we investigated the effect of insulin on leptin secretion by adipose tissue. Epididymal fat pads were incubated in vitro in the presence or absence of insulin over a 4-h time course. Insulin increased leptin secretion by about 80% at all time points studied. After 10 min of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

19
165
1
10

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(195 citation statements)
references
References 42 publications
19
165
1
10
Order By: Relevance
“…These data suggest that food intake may modulate leptin secretion and reinforce the notion that it may play a role in the process of satiety, modulating meal size (22). The increase in plasma leptin levels after feeding may be mediated, in part, by insulin, which directly stimulates the synthesis and secretion of leptin by adipocytes (23).…”
Section: Discussionsupporting
confidence: 64%
“…These data suggest that food intake may modulate leptin secretion and reinforce the notion that it may play a role in the process of satiety, modulating meal size (22). The increase in plasma leptin levels after feeding may be mediated, in part, by insulin, which directly stimulates the synthesis and secretion of leptin by adipocytes (23).…”
Section: Discussionsupporting
confidence: 64%
“…Therefore, these effects could be associated at least in part with decreased visceral fat weight. We cannot exclude the possibility that circulating levels of adipokines are regulated by other factors, such as insulin and PPAR (3,10,22), independent of fat cell size, because the improvement effects reached their values before feeding a high-fat diet.…”
Section: Discussionmentioning
confidence: 99%
“…In adipocytes, it has been reported that constitutive as well as regulated secretion of adipokines can occur independently from TGN trafficking. For example, it has been reported that leptin is directly secreted from the endoplasmic reticulum and adiponection from the Golgi cisternae (Barr et al, 1997;Xie et al, 2006). Although these latter two proteins are soluble luminal proteins, adipocytes also display complex patterns of integral membrane protein transport with several proteins undergoing various degrees of insulin responsiveness.…”
Section: Discussionmentioning
confidence: 99%